2015
DOI: 10.1177/0269881115578162
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of risperidone and haloperidol for the risk of ischemic stroke in the elderly: a propensity score-matched cohort analysis

Abstract: The evidence showed that haloperidol should be prescribed in the elderly with caution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…There are other mechanisms than interference with cardiac repolarization and development of TdP which may be of importance to explain the elevated ‘baseline risk’ for death among users of antipsychotics. These include indirect effects on metabolism and weight gain, other cardiovascular effects such as hypertension or alterations in heart rate variability, increased risk for stroke, as well as increased risk to die in cardiovascular disease by nature of their illness . Furthermore, the lack of TdP classification cannot conclude that these medicines confer no risk in relation to development of TdP arrhythmia .…”
Section: Discussionmentioning
confidence: 99%
“…There are other mechanisms than interference with cardiac repolarization and development of TdP which may be of importance to explain the elevated ‘baseline risk’ for death among users of antipsychotics. These include indirect effects on metabolism and weight gain, other cardiovascular effects such as hypertension or alterations in heart rate variability, increased risk for stroke, as well as increased risk to die in cardiovascular disease by nature of their illness . Furthermore, the lack of TdP classification cannot conclude that these medicines confer no risk in relation to development of TdP arrhythmia .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, some studies suggest a greater risk of stroke among users of first-generation antipsychotics as compared with second-generation antipsychotics [10,12]. Shin et al reported that among elderly patients, haloperidol, a first-generation antipsychotic, was associated with a greater risk of stroke as compared with risperidone, a second-generation antipsychotic [13]. However, other studies have suggested a similar risk between first-generation and second-generation antipsychotics [7,12,14] or a greater risk with second-generation antipsychotics [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Though strokes are more common among elderly individuals than among the young individuals [17], more than half of antipsychotic users are < 65 years old [18,19] and though many studies evaluating antipsychotics and the risk of stroke have been conducted in the elderly population [13,[20][21][22], relatively few have been conducted in younger populations. Mundet-Tuduri et al [8] reported a higher prevalence of stroke in adult patients using antipsychotics compared with non-users (odds ratio 2.33).…”
Section: Introductionmentioning
confidence: 99%
“…10 Another study in older adults found an increased risk of stroke with haloperidol users compared with risperidone users. 11 Risperidone is commonly prescribed for the management of delirium symptoms in older hospitalized patients and the second most studied agent. 9,12 This pilot study aimed to evaluate the feasibility of a randomized placebo controlled trial to evaluate the efficacy and safety of risperidone in the treatment of delirium.…”
mentioning
confidence: 99%
“…A cohort study observed a small increased risk of mortality with haloperidol compared with atypical antipsychotics 10 . Another study in older adults found an increased risk of stroke with haloperidol users compared with risperidone users 11 . Risperidone is commonly prescribed for the management of delirium symptoms in older hospitalized patients and the second most studied agent 9,12 …”
mentioning
confidence: 99%